Experimental investigation on the heat transfer characteristics of nanofluids in a cylindrical heat exchanger tube using quad-structured vortex generator with semi-perforations - Manova, Stephen; Leunanonchai, Witsawat; Arkadumnauy, Thana; Camci, Muhammet; Asirvatham, Lazarus Godson; Dalkilic, Ahmet Selim; Wongsatanawarid, Atikorn; Wongwises, Somchai (ELSEVIER, 2025)
The use of vortex generators to enhance the thermal performance of heat exchangers has shown great promise, especially in improving efficiency and promoting energy conservation. The proposed experimental study focuses on evaluating the thermal performance of a commercially available cylindrical heat exchanger tube with an inner diameter of 7.1 mm, using different working fluids (water and SiO2 nanofluid) and varying inlet temperatures ranging from 35 degrees C to 55 degrees C. The effect of 3D-printed vortex generator configurations (Uncut and W5d1.5) on fluid's flow heat transfer characteristics is analyzed, for different Reynolds number (5000 to 15,000), and volume concentrations (0.5 vol % to 2.0 vol %). Particularly, the vortex generator is placed at the entry of the heat exchanger tube to improve the flow behavior right from the beginning of the fluid's path which is not reported in existing literatures. Based on the experiments with plain tube, the maximum heat transfer coefficient of 22.3 kW/ m2K is noted for 2.0 vol. % at 55 degrees C, with 42.1 % enhancement when compared to water. But for the same condition, the inclusion of uncut vortex generator further enhanced the heat transfer coefficient to 24.8 kW/m2K, with the highest enhancement of 47.5 %, than the plain tube. Correspondingly, 66.7 % increase in pressure drop is noted for the uncut configuration (no semi-perforation) than the plain tube. To be specific, the heat exchanger tube, with uncut configuration improves the heat transfer performance, more than the plain tube, and tube with vortex generator having semi-perforations (W5d1.5). However, the addition of semi-perforated vortex generators resulted in less friction, as it reduces excessive turbulence, and drag. Henceforth, the results of this experimental work are expected to be an appropriate engineering guide to develop the heat exchangers in certain areas, where fluctuations in fluid's inlet temperature exist, depending on the ambient conditions.
Keywords: Heat exchanger; Vortex generator; Twisted tape; Turbulent flow; Heat transfer; Nanofluid; PERFORMANCE ASSESSMENT; TURBULENT PIPE; SQUARE; FLUIDS; FLOW; Engineering